Analysis of Community Knowledge about Dengue Hemorrhagic Fever (DHF) and DHF Prevention Measures in the Working Area of the Martoba Pematangsiantar Community Health Center - Silaen, Peterson Yosua; Sidabutar, Sondang; Irhamsyah Afif Tampubolon (Jurnal EduHealth, 2025)
Dengue Hemorrhagic Fever (DHF) is one of the important public health problems in Indonesia and often causes an Extraordinary Event (KLB) with large deaths. Dengue cases in 2022 in Pematang Siantar City amounted to 629 cases. The purpose of this study is to Identify Public Knowledge about DHF, Identify Community Actions in DHF prevention, Analyze the Relationship between Public Knowledge about DHF and Dengue Hemorrhagic Fever (DHF) Prevention Actions. The research method used is a correlation design with a cross-sectional approach and the test carried out is the chi-square test. In this study, the population was 7,030 people and the type of sample in this study was Non-probability sampling with Purposive sampling technique. where the number of samples was 99 respondents. The results of this study are There is a Relationship between Public Knowledge about DHF and Community Actions when carrying out DHF prevention in the Working Area of UPTD Puskesmas Bane where Ha is accepted obtained with a significance value (p) of 0.035 <0.05. The significance value of the analysis of the relationship between knowledge and DHF prevention measures is <0.05. The conclusion of the study is that there is a significant relationship between community knowledge about DHF and DHF prevention measures at the Bane Community Health Center UPTD. Suggestions that can be taken are that the city government and the health service team are expected to provide more detailed information about DHF knowledge and correct DHF prevention measures, and to make posters or advertisements about DHF as well as to community organizations or local RT/RW to more routinely carry out cleaning activities in the surrounding residential areas.